AYAT-AYAT TENTANG KESABARAN DALAM LUKISAN KALIGRAFI ARAB - FITRI RUSLIYANI, Drs. Yusron Wkarya,M.Pd, Drs. Abd. Hafiz,M.Pd (Serupa The Journal of Art Education, 2014)
The purpose of this paper is to describe the verses about patience. It literally contains about keistiqomaan with faith and devotion in carrying out a series of trials that God gave human life as well as the rewards for those who are patient. The final works convey the intent and purposes contained in the verses of patience through the works of art of calligraphy as a well to better undestand and explore the greatness and power of God through the work of calligraphy. In making the work with the theme “patience verses in Arabic calligraphy painting”, the authors present aconcept forms, how said, and the media put more emphasis on the meaning of color resulting from mixing the basic colors for the display of color from dark to light will regard to the elements and priciples of art, so that the resulting ten work entitled: The rewards for those who are patient, God is with those who patiently, Leaders who provide guidance, Allah loves those who are patient, Patient and devoted, On the border land, God news, signs of God's power, People who win, and Patient.Keywords: Verses about patient, Arabic caligraphy